2021
DOI: 10.3390/ijerph18189919
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Endometriosis Symptoms—A Cross Sectional Survey among Polish Women

Abstract: Background: Endometriosis is a chronic inflammatory condition characterized by the presence of endometrial-like tissue outside of the uterine cavity. It affects approximately 6–12% among reproductive-age women. Laparoscopy is still the gold standard for diagnosing it. Since an average of couple of years elapses from the onset of symptoms to the definitive diagnosis, analysis of symptoms could serve as a non-invasive diagnostic tool. Methods: An anonymous survey was distributed online in November 2019. It conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…In this study, we found that 23.1% of OMA patients manifested no dysmenorrhea, which was in agreement with previous findings that 17–39% of OMA patients could be non-dysmenorrhea ( 10 – 12 ). According to our results, baseline characteristics such as age, BMI, parity, and gravidity showed no difference between the two groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that 23.1% of OMA patients manifested no dysmenorrhea, which was in agreement with previous findings that 17–39% of OMA patients could be non-dysmenorrhea ( 10 – 12 ). According to our results, baseline characteristics such as age, BMI, parity, and gravidity showed no difference between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Dysmenorrhea, together with infertility, constitutes the major clinical complication in OMA patients ( 8 , 9 ). However, about 17–39% of OMA patients do not present any complaint of dysmenorrhea ( 10 – 12 ). Hence, whether dysmenorrhea symptoms would correlate with clinical characteristics and postoperative outcomes in this subset of OMA patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This study agree with many previous study as (Kotowska et al, 2021), (Adewunmi & Sasah, 2022. ), (Arab et al, 2022), (Henry et al, 2022), (Kotowska et al, 2021), (Le Busque & Mellish, 2023), (S. L. Mohamed El Sayed et al, 2022), (Ramani Devi et al, 2021), (Roullier et al, 2021), (Szymańska & Dąbrowska-Galas, 2021), (Wróbel et al, 2022), (Khan et al, 2022), (Sodeinde & Konu, 2022), (Randhawa et al, 2021), (Henry et al, 2022), (Navarria-Forney et al, 2020), (Mohamed & Hassan, 2020. ), (Mecha et al, 2022), (Eldardery et al, 2022), (Abd Elrahim et al, 2022), (Adewunmi & Sasah, 2022.…”
Section: Theoretical Reviewsupporting
confidence: 94%
“…Since the search for a non-invasive diagnostic endometriosis marker has been conducted for many years without success so far, it seems that awareness of the clinical presentation and reported symptoms may help to provide earlier diagnoses. (Kotowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is scarce evidence that iatrogenic endometriosis behaves or develops differently from non-iatrogenic endometriosis, since the general clinical presentation and patient complaints with endometriosis mostly include dysmenorrhea, dysuria, dyschezia, chronic pelvic pain, and infertility [ 11 ]. These factors serve as indicators for treatment [ 12 ]; thus, the care of iatrogenic endometriosis can significantly differ from that of non-iatrogenic endometriosis by the main medical or surgical approach.…”
Section: Introductionmentioning
confidence: 99%